Microfacies, depositional environment and diagenetic evolution controls on the reservoir quality of the Permian Upper Dalan Formation, Kish Gas Field, Zagros Basin. (November 2015) - Amel, Hamed; Jafarian, Arman; Husinec, Antun; Koeshidayatullah, Ardiansyah; Swennen, Rudy
Abstract: The Upper Permian Upper Dalan Formation contains one of the largest gas reservoirs in the world. The formation consists of carbonates with some evaporite intercalations that developed on a gently sloping homoclinal carbonate ramp facing the Late Permian Paleo-Tethys Ocean. This study focuses on the Kish Gas Field (Zagros offshore basin situated between Iran and Qatar), and is based on a 222-m-thick continuous core. Based on the integration of core- and wireline-log data coupled with petrographic analyses of 580 thin sections, three major depositional environments (facies belts) with 11 carbonate microfacies are identified. These include (1) sabkha to tidal flat (laminated to massive anhydrite, dolomudstone with anhydrite nodules, dolomudstone, and intraclastic dolowackestone), (2) lagoon and leeward shoals (bioclastic wackestone/dolowackestone to packstone, and peloid dolopackstone and peloid–bioclastic dolopackstone), and (3) mobile (windward) sand shoal (ooid–peloid dolograinstone, ooid dolograinstone, ooid–intraclast dolograinstone, ooid–bioclast dolograinstone–packstone, and coarse bioclast–intraclast dolograinstone). Diagenetic evolution of the Upper Dalan Formation is associated with evaporative marine, shallow-water normal-marine, meteoric, and burial diagenetic environments. Common diagenetic effects include dolomite and calcite cementation, mechanical and chemical compaction, dissolution, dolomitization, and evaporative (anhydrite) mineralization. Reservoir quality is strongly affected by variations in the original rock fabrics and subsequent diagenetic alterations. The most common pore types include interparticle, moldic, and connected vug (fracture and cavernous). The interparticle porosity–permeability relationship for the studied facies suggests that the reservoir quality is not affected by different crystal sizes and most samples plot in the low porosity and low to high permeability field, or display Lucia class 1 or 2 petrophysical relationships. The study shows that the pervasive pore-filling anhydrite mineralization lead to a significant decrease in porosity and permeability; poikilotopic anhydrite cement reduced matrix porosity, but the pore size was less affected. Highlights: First study of the Upper Dalan Formation in the Kish Gas Field, Zagros Region. Depositional Model for the Upper Dalan Formation is established. Diagenetic history suggests four different diagenetic settings. Microfacies and diagenetic effects on reservoir quality are evaluated.